Acromegaly or chronic renal failure: a diagnostic dilemma. - Wong, N; Ahlquist, J; Camacho-Hübner, C; Goodwin, C; Dattani, M; Marshall, N; Wass, J (1997)
Uraemic patients may have markedly elevated serum GH concentrations yet, for hitherto unknown reasons, they do not develop acromegaly. We discuss the diagnostic dilemma presented by a 33-year-old Caucasian male with chronic renal failure (creatinine clearance 10 ml/min) secondary to polycystic kidney disease, elevated GH concentrations (fasting concentration of 22.6 rising to 77.9 mU/l 30 minutes after a 75-g oral glucose load) as well as acromegalic features. Review of the patient's relatives and the findings of a normal serum IGF-I concentration and a normal pituitary fossa on magnetic resonance imaging, suggest that the patient's acromegalic appearance is a familial trait and his abnormal GH dynamics a result of his renal failure rather than acromegaly. The patient's normal GH bioactivity and reduced GH binding protein concentration supports the current belief that chronic renal failure leads to an increase in peripheral tissue resistance to GH due to decreased GH receptor numbers. These changes, together with reduced IGF-I bioactivity, may explain why patients with chronic renal failure do not develop acromegaly in the presence of abnormally elevated levels of GH.